Isolation and characterization of a presynaptic neurotoxin, P-elapitoxin-Bf1a from Malaysian bungarus fasciatus venom - Ahmad Rusmili, Muhamad Rusdi; Ting, Tee Yee; Mustafa, Mohd Rais; Hodgson, Wayne C.; Othman, Iekhsan (Elsevier Inc., 2014)
Presynaptic neurotoxins are one of the major components in Bungarus venom. Unlike other Bungarus species that have been studied, β-bungarotoxin has never been isolated from Bungarus fasciatus venom. It was hypothesized that the absence of β-bungarotoxin in this species was due to divergence during evolution prior to evolution of β-bungarotoxin. In this study, we have isolated a β-bungarotoxin isoform we named P-elapitoxin-Bf1a by using gel filtration, cation-exchange and reverse-phase chromatography from Malaysian B. fasciatus venom. The toxin consists of two heterogeneous subunits, subunit A and subunit B. LCMS/MS data showed that subunit A was homologous to acidic phospholipase A2 subunit A3 from B. candidus and B. multicinctus venoms, whereas subunit B was homologous with subunit B1 from Bungarus fasciatus venom that was previously detected by cDNA cloning. The toxin showed concentration- and time-dependent reduction of indirect-twitches without affecting contractile responses to ACh, CCh or KCl at the end of experiment in the chick biventer preparation. Toxin modification with 4-BPB inhibited the neurotoxic effect suggesting the importance of His-48. Tissue pre-incubation with monovalent B. fasciatus (BFAV) or neuro polyvalent antivenom (NPV), at the recommended titer, was unable to inhibit the twitch reduction induced by the toxin. This study indicates that Malaysian B. fasciatus venom has a unique β-bungarotoxin isoform which was not neutralised by antivenoms. This suggests that there might be other presynaptic neurotoxins present in the venom and there is a variation in the enzymatic neurotoxin composition in venoms from different localities.